Can socioeconomic disadvantage explain cognitive differences in later life? Insights from the Indonesia family life survey - Sujarwoto, Sujarwoto; Yumarni, Tri; Holipah, Holipah; Maharani, Asri (Frontiers in Public Health, 2025)
IntroductionCognitive decline, including cognitive impairment non-dementia (CIND) and dementia, is a growing public health concern, particularly in ageing populations within developing countries. Socioeconomic status (SES) is increasingly recognized as a key determinant of cognitive ageing, yet evidence from low- and middle-income contexts remains limited. This study investigates the relationship between SES and later-life cognitive outcomes in Indonesia.MethodsWe analysed longitudinal data from Waves 4 and 5 of the Indonesia Family Life Survey (IFLS), involving 3,087 participants aged 50 years and older at baseline (Wave 4). Cognitive outcomes, including CIND and dementia, were assessed seven years later using an adapted version of the Telephone Interview for Cognitive Status (TICS). Multilevel ordinal regression was employed to evaluate the association between SES indicators at baseline—such as education, income, residential location, and participation in community-based older adults health posts (Posbindu Lansia)—and subsequent cognitive outcomes.ResultsAt follow-up, 38% of the sample exhibited CIND, and 19% were classified as having dementia. Higher levels of formal education, greater income, urban residence, and engagement in Posbindu Lansia activities were significantly associated with reduced risk of both CIND and dementia.DiscussionFindings suggest that SES disparities contribute to cognitive decline in later life. Interventions aimed at improving educational attainment, economic conditions, and community health access among older adults may serve as critical strategies to mitigate the future burden of dementia. Reducing social inequalities in health should therefore be prioritized in dementia prevention policies within low-resource settings.